Empowerment of pioneer students of small ambassadors in health promotion at SD Negeri Karangroto 02 Semarang City - Nutrisia Nuim Haiya; Iwan Ardian; Intan Rismatul Azizah (Universitas Muhammadiyah Magelang, 2022)
Schoolchildren are assets for the Indonesian state, and in order to accomplish this, school health unit, or UKS, must be developed and maintained. However, in order for UKS to succeed, it needs the assistance of all essential stakeholders, including students, throughout its implementation. As a result, the effective implementation of UKS necessitates a cadre of students who serve as one of the spearheads. Indirectly, health cadres serve as role models for promoting health in the school community and environment. The objective of empowering health cadres is to ensure the success of the UKS program and to promote school health. This practice also attempts to enhance all students' knowledge, attitudes, and behaviors. The service approach entails empowering the community via the formation of Pelopor Siswa Duta Kecil (SiDuCiL), a non-profit organization dedicated to promoting health through the training of school health cadres. As a consequence of this activity,